TINJAUAN YURIDIS PELAKSANAAN IZIN ALIH FUNGSI LAHAN PERTANIAN KE NON PERTANIAN DI KABUPATEN PINRANG - Asram A.T.Jadda, Sadriyah Mansur, Sitti Rahma Haeruddin (Madani Legal Review, 2021)
This study aims to determine the implementation of permits for conversion of agricultural land to non-agricultural and law enforcement against violations of permits for conversion of agricultural land to non-agricultural functions in Pinrang Regency. This research uses descriptive qualitative research with an empirical normative approach. Data obtained from the results of literature studies and interviews. The results of this study indicate that the implementation of permits for conversion of agricultural land to non-agricultural functions in Pinrang Regency has been carried out in accordance with applicable laws and regulations where not all permit applications are granted, the granting of permits must be in accordance with the established Regional Spatial Plan (RTRW). The obstacles that cause the implementation of permits have not been maximized due to the lack of comprehensive socialization and the lack of responsiveness of the community in complying with licensing procedures. Law enforcement of violations of permits for conversion of agricultural land to non-agricultural functions in Pinrang Regency has also been carried out but has not been maximized. The sanctions given to people who violate permits are still not firm and do not cause a deterrent effect.